“BABAR LONTAR” STRATEGI GELIAT BUDAYA PELESTARIAN LONTAR DI BALI PADA MASA PENDEMI COVID-19 - Putu Dedi Handana (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2021)
The importance of knowing, studying, and disseminating the existence of lontar as astrategy to preserve ancestral heritage so that it can be a reference source for informationrelated to previous human civilizations from various aspects of life, such as cultural, social,agricultural, medical, and so on, is very important. Efforts have been made to physicallymaintain the presence of lontar so that it is not easily damaged and can still be read as a sourceof cultural heritage. In the midst of the Covid-19 pandemic, all activities are starting to belimited, but active to disseminate the existence of lontar manuscripts is no longer a taboo thingbut as something that must be known so that the perception of